PENGARUH MANAJEMEN KEPALA SEKOLAH DAN PROFESIONALISME GURU TERHADAP KINERJA GURU (STUDI KASUS PADA SMK BINA MANDIRI KABUPATEN TANGERANG) - syavinayati (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This research aims to determine the influence of school principal management and teacher professionalism on teacher performance at SMK Bina Mandiri, Tangerang Regency. The population in this study is the teachers of SMK Bina Mandiri. The sample size was 45 respondents. The research method uses a quantitative method. The sampling technique uses saturated sampling. Based on the research results, it shows that there is a significant influence between school principal management and teacher performance. This is evidenced by the Sig. value of 0.002 < 0.05 and t-value = 3.393. There is a significant influence between teacher professionalism and teacher performance. This is evidenced by the Sig. value of 0.000 < 0.05 and t-value = 11.122. And there is a significant influence between school principal management and teacher professionalism together on teacher performance. This is evidenced by the Sig. value of 0.000 < 0.05 and F = 120.059.